Usaha Pemanfaatan Kain Kanvas dan Perca Endek sebagai Tas yang Bernilai Seni - Komalayakti, Diah; Gunawan, I Wayan; Jodog, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Endek is a traditional Balinese cloth that has a variety of motifs such as stylization of flora and fauna. Now many endek fabrics are also designed into clothing such as official clothes and so on. So, in the process of making these clothes, of course, there will be a lot of leftover patchwork for making clothes. Therefore, innovation in the form of using patchwork with canvas is an effort to preserve the existence of endek with bag products as a fashion complement. Bags are a fashion item that cannot be separated from the daily style of teenagers. The creation of bag products is done by self-manufacturing. So, of course, has a high artistic value. The selected bag design is a consideration of the uniqueness and tastes of the community, especially teenagers. The process of creating something so that it can add value in the economy is the meaning of entrepreneurship. In that case, the creation of a product with innovation and creativity is very important. The use of endek textiles and patchwork into a product in the form of a bag is an innovation in the creative industry and develops creativity. In addition, efforts to preserve the existence of endek in the midst of modern times that orient modern culture as a fashion trend can be done by collaborating with emerging trends.